THE URGENCY AND FINANCIAL SERVICES SECTOR DISPUTE SETTLEMENT MECHANISM THROUGH ALTERNATIVE DISPUTE SETTLEMENT INSTITUTIONS - Aprinisa (Faculty of Law-Universitas Bandar Lampung, 2022)
Settlement of disputes that occur between Consumers and Financial Services Providers can not only be done through litigation (court) but there are also other options through Alternative Dispute Resolution (non-litigation) channels which are commonly called APS. The choice of dispute resolution through APS is an answer to the needs of Financial Services Enterprises and consumers since it is efficient, effective, and low cost so that it can reduce operational costs. In addition, with the support of sophisticated dispute resolution technology through the Financial Services Sector Alternative Dispute Resolution Institution, the disputing parties do not have to meet face-to-face but it can be done using electronic media. The method used in this research is a normative juridical study, by examining the norms/rules contained in the legislation and library materials. The study in this research is about the urgency and mechanism of dispute resolution through the Alternative Dispute Resolution Institution in the Financial Services Sector.